Raising Students’ Executive Cognitive Function through Students-Centered Learning Approach in Teaching Creative Writing - Emanuella Christine Natalia Mau (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2019)
Aristotle once said that art is the imitation of life. Therefore, art production is similar to mimic society and life itself. Writing, one of art productions, needs to also mirroring human life and society. Revolution Industry 4.0 has demanded human to be more creative and digitally literate. It also demands a shifting paradigm to teach the millennial students in the 4.0 revolution industry. The millennial students, according to Millennials Go To College (2003) by Neil Howe and William Strauss, shows characteristics as follows: special, sheltered, confident, team-oriented, achieving, pressured, and conventional. Those characteristics need to be supported by good skills of Executive Cognitive Function in their learning to survive the 4.0 revolution industry. Thus, this paper is written to see the contribution of Student-Centered Learning in facilitating the millennial students’ through collaborative and co-operative learning in raising the Executive Cognitive Function skills in creative writing course. Key words: Executive Cognitive Function; Student-Centered Learning; Collaborative Learning; Co-operative Learning